Ambivalent Food Craving and Psychobiological Characteristics in Individuals With Weight Suppression - Lee, Mooah; Lee, Jang-Han (Frontiers in Psychology, 2021)
This study investigated the effects of psychobiological characteristics of non-obese women with a high level of weight suppression on explicit-implicit and approach-avoidance response toward food cues, depending on hunger-satiety states. The 634 participants were divided into two groups according to their weight history. If the difference between their highest weight over the last year and their current weight (a difference sustained at least for one year) was more than 5%, they were assigned to the “high level of weight suppression” (H-WS) group (N = 25). If the difference in weight was less than 5%, they were assigned to the “low level of weight suppression” (L-WS) group (N = 29). Explicit approach and avoidance toward food were measured by self-report questionnaires. Implicit approach and avoidance toward food cues were measured using an eye-tracker. Fasting blood samples were obtained to measure fasting serum leptin levels. After this, participants consumed a standard breakfast to control the satiety level. After breakfast, explicit-implicit approach-avoidance responses were repeatedly measured at the satiety states. Self-reported body shape concerns, drive for thinness, ambivalent food craving, and bulimic behavior were also assessed. The results showed that the H-WS group had lower leptin levels, and higher body shape concerns, drive for thinness, ambivalent food craving, and bulimic behaviors compared to the L-WS group. At the explicit level, the H-WS group reported lower approach and higher avoidance to food compared to the L-WS group, regardless of hunger-satiety state. Whereas, at the implicit level, the H-WS group showed higher approach during satiety rather than during hunger states. Regardless of the hunger-satiety state, there were no significant group differences with regard to implicit avoidance between the two groups. Thus, we confirmed that a high level of avoidance toward foods was observed in the H-WS group at the explicit level but not at the implicit level. Moreover, in contrast with a high level of explicit avoidance toward palatable foods, inhibition for implicit approach toward high-calorie foods seemed to be blunted after food consumption in the H-WS group. These inconsistencies may be associated with ambivalent food craving and vulnerability to bulimic behavior among H-WS individuals.